2022
DOI: 10.1001/jamapediatrics.2021.4565
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority and Safety of Nadolol vs Propranolol in Infants With Infantile Hemangioma

Abstract: IMPORTANCE Propranolol for infantile hemangiomas (IH) has been shown to be effective and relatively safe. However, other less lipophilic β-blockers, such as nadolol, may be preferable in individuals who experience propranolol unresponsiveness or adverse events. OBJECTIVE To document the noninferiority and safety of oral nadolol compared with oral propranolol in infants with IH.DESIGN, SETTING, AND PARTICIPANTS This double-blind noninferiority prospective study with a noninferiority margin of 10% compared propr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Oral atenolol can be used as an alternative treatment option for IH patients requiring systemic therapy (18). Another randomized controlled trial also showed that oral nadolol was noninferior to oral propranolol, indicating it may be an efficacious and safe alternative in cases of propranolol unresponsiveness or adverse events, or when faster involution is required (19).…”
Section: Discussionmentioning
confidence: 99%
“…Oral atenolol can be used as an alternative treatment option for IH patients requiring systemic therapy (18). Another randomized controlled trial also showed that oral nadolol was noninferior to oral propranolol, indicating it may be an efficacious and safe alternative in cases of propranolol unresponsiveness or adverse events, or when faster involution is required (19).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies continue to demonstrate the safety and efficacy of propranolol as well as other beta-blockers including atenolol, 18,19 nadolol, 20 and topical timolol 21 . Most studies have used a goal dose of 2 to 3 mg/kg/d of propranolol 14 .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to oral treatment may be patches with propranolol ( Musazzi et al, 2021 ). Nadolol can be an effective and safe alternative to propranolol ( Pope et al, 2022 ). Also in the treatment of subglottic hemangiomas, propranolol and nadolol have been shown to be equally effective ( Yang et al, 2021 ).…”
Section: Propranolol–an Old Drug With New Propertiesmentioning
confidence: 99%